Impact of central venous pressure during the first 24 h and its time-course on the lactate levels and clinical outcomes of patients who underwent coronary artery bypass grafting - Zhao, Yu; Zhang, Hongmin; Wang, Xiaoting; Liu, Dawei (Frontiers in Cardiovascular Medicine, 2023)
Background: Prior studies have shown that elevated mean central venous pressure (CVP) in certain patient populations associated with poor prognosis. But no study explored the impact of mean CVP on prognosis of patients underwent coronary artery bypass grafting surgery (CABG). The aim of this study was to investigate the impact of elevated central venous pressure and time-course of central venous pressure on clinical outcomes of patients underwent coronary artery bypass grafting surgery and potential mechanisms. Methods: We performed a retrospective cohort study based on the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. We first identify the CVP of specific period with the most predictive value. Patients were categorized into low_cvp and high_cvp group according to the cut-off value. We used propensity score matching (PSM) to adjust covariates. The primary outcome was 28-day mortality. Secondary outcomes were 1-year and in-hospital mortality, the length of ICU stay and hospitalization, AKI incidence, vasopressors use, duration of ventilation and oxygen index, and lactate levels and clearance. Patients in the high_cvp group were categorized into the “Second day CVP≤13.46mmHg” group and the “Second day CVP＞13.46mmHg” group respectively, and the clinical outcomes were the same as before. Results: The mean CVP during first 24 hours was the most correlative and statistically significant for 28-day mortality. The risk of 28-day mortality was increased in the high_cvp group (OR 3.45 (95% CI 1.77–6.70; p < 0.001)). Poor secondary outcomes were also associated with elevated CVP levels. The maximum of lactate levels and lactate clearance were also poor in high_cvp group. For patients in the high_cvp group during first 24 hours, whose mean CVP during the second day lowered to less than cut-off value had better clinical outcomes. Conclusions: Elevated mean CVP during first 24 hours was correlated with poor outcomes in patients underwent CABG. The potential mechanisms maybe influencing the lactate levels and lactate clearance through the impact on afterload of tissue perfusion. Patients whose mean CVP during the second day dropped to less than the cut-off value had favorable prognosis.